(3MGTjI Ydi TQM GdCdajI ddCTehfjs - (3CHh GdYQaGf, GdUHGf, eMeO Hf Ydj, (B1206 (3g`s
(3ChdgG (B:s
(3fMeOc Gddge Ydi eG hLgJ fMhfG ef ShGHZ GdfYeCeG HYO ajbhdeMeO Hf Ydj GdUHGfgPg MhGTjNOeJ HgG TQM GdCTehfj Ydi CdajI GHf eGdcs
(3BNQgG (B:s
(3fGbU GdBNQ, hBNQg(B: (3gfG eJYdbGf HaYd aJchf GdUdI MjfFP LedI adG MGLI dbhdg Ch THggG EdG Cf jbGd eQGOg HGdLedI aj bhdg hLedI GdedahX hTHHgG GdLedI GdebOQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 6 / 297s
(3eYLe GdeDdajf(B: 3 / 516s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdfMhs